Cardiometabolic Risk: Current Perspectives and Future Aims - Sinclair, Heather Q. (MD Conference Express, 2010)
Cardiometabolic risk assessment has become a key component to these new management strategies. Many of these risk factors can be alleviated with lifestyle modification and diet adjustments. Over the past decade, trial data have broadened our understanding of cardiometabolic risk as it applies to diabetes and other health issues.